SISTEM PAKAR DIAGNOSA KERUSAKAN PADA KOMPUTER TABLET (Information Technology and Telematics, 2013)
Abstract-- Tablet computer is a hardware device that vulnerable to damage,  however  tablet  computer  can  last  a  long  if  cared  for properly,   by   not   ignoring   mild   damages.   In   providing   that information, it takes an expert on knowledge of the tablet computer. Where  an  expert  system  designed  for  the  tablet  computer  as  a computer  program, so the expert system program can provide information such as a computer expert who always stood beside the tablet computer itself. Expert system for damage  tablet computers will provide a solution for tablet computer users on issues relating thereto. Keywords: Expert System, Computer Tablet, PHP,M ySQL